Ectopic lymphoid follicles in progressive multiple sclerosis: From patients to animal models. Issue 3 (2nd August 2021) - Zhan, Jiangshan; Kipp, Markus; Han, Wenling; Kaddatz, Hannes
Abstract: Ectopic lymphoid follicles (ELFs), resembling germinal centre‐like structures, emerge in a variety of infectious and autoimmune and neoplastic diseases. ELFs can be found in the meninges of around 40% of the investigated progressive multiple sclerosis (MS) post‐mortem brain tissues and are associated with the severity of cortical degeneration and clinical disease progression. Of predominant importance for progressive neuronal damage during the progressive MS phase appears to be meningeal inflammation, comprising diffuse meningeal infiltrates, B‐cell aggregates and compartmentalized ELFs. However, the absence of a uniform definition of ELFs impedes reproducible and comparable neuropathological research in this field. In this review article, we will first highlight historical aspects and milestones around the discovery of ELFs in the meninges of progressive MS patients. In the next step, we discuss how animal models may contribute to an understanding of the mechanisms underlying ELF formation. Finally, we summarize challenges in investigating ELFs and propose potential directions for future research. Abstract : ELFs are frequently found in the meninges of the deep sulci in about 40% of investigated progressive MS tissues. The typical structure of organized ELFs resembles the architecture of germinal centres in secondary lymphoid organs. In addition to compartmentalized B‐ and T‐cell zones, ELFs also feature specialized TFH cells, which are in close contact to B cells (predominantly CD27 + memory B cells), as well as follicular dendritic cells (FDC), which are essential for B‐cell differentiation and activation.